WORKING IN JAPAN AS A TRAINEE: THE REALITY OF INDONESIAN TRAINEES UNDER JAPAN'S INDUSTRIAL TRAINING AND TECHNICAL INTERNSHIP PROGRAM - NFN Nawawi (Research Centre for Population, Indonesian Institute of Sciences, 2010)
Attracted by Japan's prosperity and motivated by desire for gaining higher income, many Indonesians have been migrating to Japan in increasing numbers since the mid-1990s. Different from other destination countries, most of Indonesian workers who came to Japan is under the program called